Decline in Brahman Breed Influence of Beef Calf Lots Marketed by Video Auction from 1995 to 2015 - E. D. McCabe; M. E. King; K. E. Fike; K. L. Hill; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2017)
Brahman cattle are widely known for their ability to tolerate hot and humid climates as well as for their insect and parasite resistance. An estimated 40% of all beef cows in the United States are located in the southern region, which has a relatively hot climate. Historically, many of these beef cows have had at least some Brahman influence. The opportunity to evaluate potential changes in the influence of the Brahman breed on beef calves produced in the United States was available through lots of beef calves marketed through a video auction service. The objective was to characterize the potential change in the percentage of lots of beef calves with Brahman influence among calves originating from various regions of the United States marketed through summer video auctions from 1995 through 2015.
Keywords: beef calves; Brahman influence; video auctions